The Role of Sentinel Lymph Node Biopsy in the Management of Breast Cancer (Journal of Bangladesh College of Physicians and Surgeons, 2015)
The sentinel lymph node (SLN) is defined as the first node(s) receiving lymphatic drainage from a primary tumour. A promising alternative to axillary lymph node dissection (ALND) is sentinel lymph node biopsy. SLN biopsy has been introduced as a technique to identify axillary lymph node most likely to contain tumour cells metastasizing from a primary carcinoma of breast. Several methods of identifying the SLN exists, including the use of radioactive tracer, lymphazurin dye or combination of the two via intraparenchymal and/or intradermal, peritumoral or periaerolar injection sites. Intraoperative evaluation of SLNs are done by performing FS(Frozen Section) on all the lymph nodes after serially sectioning them at 3-4mm intervals; at least 2 levels are cut of all the sentinel lymph nodes. In addition, touch preparation cytology(TP) smear may also be made for evaluation. The limitations of SLNB is that a proportion of patients who have metastasis limited to the SLN can be predicted when there is a combination of tumour size